FTIR Analysis of MgO/TiO2 Nanocomposite on Adsorption of Remazol Turquoise Blue Dye - Muhammad Abdus Salam Jawwad; Restu Hikmah Ayu Murti; Ya-Fen Wang; Sheng-Jie You (Nusantara Science and Technology Proceedings)
A magnesium oxide and titanium (II) oxide nanocomposite, MgO/TiO2 was synthesized to improve its surface area thus its adsorption capability may be risen. The synthesis was applying sol-gel method, combining MgO and TiO2 nanoparticles with NaOH becomes a nanocomposite with higher surface area. Characterization using FTIR were carried out. The expectation of using MgO/TiO2 compared with TiO2 and MgO alone is it may react faster on an adsorption trial with remazol turquoise blue dye, and the TiO2 may give its photocatalysis ability to the synthesized material. The FTIR analysis results show that the MgO and TiO2 are successfully combined become MgO/TiO2 nanocomposite. On adsorbing remazol blue, MgO/TiO2’s surface is chemically influenced by the dye’s C=O and amides group.